Compressive Strength of Thin-Walled Cellular Core by Inkjet-Based Additive Manufacturing - Zhou, H. F. (2016)
Lightweight honeycomb structures are widely used in aerospace industry and sporting protective equipment. Commercially available honeycomb cores often come in the basic hexagonal cell shape. In this present work, variation of unit cell shapes such as hexagons, triangles and circles were fabricated by inkjet-based additive manufacturing (AM) using photopolymer materials. Inkjet-based AM is able to manufacture thin walled products with high dimensional stability and hence it is suitable to fabricate thin-walled honeycomb core. In this paper, flatwise compression tests were performed on various geometrical parameters with constant relative density. The results obtained show that the compressive properties of honeycomb are largely affected by the cell shapes.